Life-Threatening Manifestation of Diarrhea - Haritha Chelimilla; David Widjaja; Simeon Carvajal; Kavitha Kumbum (Case Reports in Infectious Diseases)
Acute diarrhea is usually mild and self-limited in normally healthy individuals. Further diagnostic evaluation is indicated in patients with severe diarrhea. We present a case of a 46-year-old woman who presented with dehydration and acute renal failure due to acute severe diarrhea. Initial stool study was suggestive of Aeromonas. Further stool test revealed offending bacteria, which led to appropriate antibiotic use. This paper emphasizes the importance of complete history and correlation between clinical data and laboratory tests.